The Effect of Israeli Apartheid Wall on the Palestinian Society from Economic and Social Aspects - Sharabati, Abdel-Aziz; Sharabati, Nadia (Jordan Journal of Social Sciences, 2021)
The aim of this research is to study the impact of the Apartheid Wall on the Palestinian society from the economic and social point of view. For this purpose, data were collected from various sources such as books, research, previous studies, master’s thesis, doctoral dissertations, UN resolutions, and reactions from governmental and non-governmental bodies. The study found that there is a great impact on the daily life of Palestinian society, as it has exacerbated the economic and social crisis, as the construction of the wall has led to the destruction and disruption of many Palestinian economic facilities, which has contributed to the rise in unemployment and poverty.